De autonomías y superposiciones. En torno a los usos de Bourdieu en la historiografía sobre intelectuales y política en la Argentina de los sesenta-setenta - Starcenbaum, Marcelo (2013)
The order you want to achieve in this work is to reconstruct the uses of Bourdieu's work on the historiography of intellectuals and politics in Argentina between 1960 and 1970. Through reading of the major works on this subject, we will analyze the place that occupied the Bourdieu's perspectives in formulating a model of intellectual sixties, politically engaged but with autonomous cultural interventions, and a model of the seventies, whose cultural creations were subordinated an absolute commitment to the policy